Extraction, Phytochemical Analysis, and Antioxidant Activity of Adhatoda vasica Leaves - Kamal, Hameed Fathima; Mahendra, Jaideep; Pandurangan, Ashok Kumar (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Adhatoda vasica is a well-known medicinal plant with diverse therapeutic properties, widely used in traditional medicine. Its phytochemical composition and antioxidant potential warrant detailed investigation. Objectives: This study aimed to evaluate the extraction efficiency, phytochemical profile, and antioxidant activity of aqueous and ethanolic leaf extracts of Adhatoda vasica. Materials and Methods: Aqueous and ethanolic extracts of Adhatoda vasica leaves were prepared using standard extraction procedures. Phytochemical screening was conducted to detect the presence of bioactive compounds such as saponins, flavonoids, tannins, and alkaloids. Liquid Chromatography-Mass Spectrometry (LCMS-MS) analysis was performed to identify bioactive constituents. Antioxidant activity was assessed using DPPH and ABTS radical scavenging assays, with naringenin used as a positive control. Results: Phytochemical analysis confirmed the presence of key secondary metabolites in both extracts. LCMS-MS analysis identified a total of 153 bioactive compounds, with a greater number detected in the ethanolic extract compared to the aqueous extract. Antioxidant assays demonstrated that the ethanolic extract exhibited significant free radical scavenging activity in a concentration-dependent manner, comparable to the standard naringenin. Conclusion: The findings indicate that Adhatoda vasica leaves are a rich source of bioactive compounds with potent antioxidant activity. The ethanolic extract, in particular, shows promising potential for the development of natural therapeutic agents targeting oxidative stress-related disorders. Further studies are needed to explore the pharmacological applications of these compounds.
Keywords: ABTS; Adhatoda vasica; Antioxidant; DPPH; LCMS-MS